Vigilancia de la salinidad del suelo en cultivos de arroz en Lambayeque, periodo 2001-2014 utilizando imágenes de satélite y conductividad eléctrica - Sigueñas, Rodrigo (2019)
The objective of this research work is to esrtimate soil salinity in rice crop areas in Lambayeque district and investigate the temporal and spatial behavior, using ETM+ sensor (LandSat-7) satellite images, MODIS sensor (TERRA) and data obtained from electrical conductivity (EC) of the soil in situ. For this purpose, normalized dierence vegetation index (NDVI), soil salinity index (IndSal) and the standardized anomaly of the NDVI were the analysed parameters. The maximun compound value (MVC) analysis of the NDVI and soil salinity index, the standard deviation of the NDVI and soil salinity index from ETM+ sensor and standardized anomalies from ETM+ and MODIS sensors allowed to separate high quality soils from those with salinity problems. Based on the MVC de NDVI and soil salinity index it was obtained 12 864.24 ha and 12 567.96 ha respectively belonging to rice crop areas, the standard deviation of NDVI and IndSal resulted in 12 692.16 ha and 12 250.53 ha of rice crop areas respectively, the detected area by means of electrical conductivity of the soil, belonging to non saline and slightly saline is of 12 661.02 ha. A shapele was achieved from each analysed area, layer the temporary variation of NDVI was obtained from MODIS sensor, through which it was reached the seasonal index (SI) and its correlation (R) with the rice crop data (harvested area, producción and crop yields) provided by the Ministry of Agriculture and Irrigation (MINAGRI) were particularly signicant (0.74 - 0.90), this shows that the analysed areas belong to rice crops. Once the rice crop areas were detected, the temporary variation of the electrical conductivity of the soil between 2001-2014 was obtained.